Pendekatan Konseling Rational Emotive Behavior Therapy (REBT) untuk Meningkatkan Motivasi Belajar Siswa: RATIONAL EMOTIVE BEHAVIOR THERAPY (REBT) COUNSELING APPROACH TO IMPROVE STUDENTS' LEARNING MOTIVATION - Marwah, Marsha Siti; Sulistiyawati, Wiwin; Hayati, Lulu; Agnia, Bita; Khairat, Imalatul (Innovative: Journal Of Social Science Research, 2025)
This study aims to explain how the Rational Emotive Behavior Therapy counseling approach can be used to improve students' learning motivation. The method used in this study is literature review by examining various relevant sources. The analysis technique applied is descriptive analysis of the theory and practice of REBT in the educational context. The results show that this approach helps students recognize and replace irrational beliefs that hinder the learning process with more rational and constructive beliefs. Through the ABCDEF technique, students can understand the relationship between events, beliefs, and emotional consequences, and develop healthier and more logical thinking patterns. The recommendation from this study is that guidance and counseling teachers implement the REBT approach as an effective service strategy to help students enhance their learning motivation and achieve emotional balance. Keywords: Learning motivation, counseling, Rational Emotive Behavior Therapy